2004
DOI: 10.1038/sj.cdd.4401404
|View full text |Cite
|
Sign up to set email alerts
|

BMP controls nitric oxide-mediated regulation of cell numbers in the developing neural tube

Abstract: Balanced cell proliferation and cell death determines neural precursor cell numbers in early stages of neural tube (NT) development. We have previously shown that nitric oxide (NO) regulates cell numbers locally in the NT of eight to 12 somite embryos. Here, we demonstrate that bone morphogenetic protein-4 (BMP-4), which is expressed in the ectoderm and dorsal NT at these developmental stages, induces programmed cell death (PCD) and promotes entry into the S-phase, via nitric oxide synthase (NOS) activity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In mammalian brain, NO may regulate neural progenitor proliferation and differentiation by acting in a positive feedback loop with BDNF [22]. Most recently, it was reported that BMP4 regulate cell numbers in the developing neural tube in a NO dependent manner [113]. Consistent with this finding, an independent study reported that inhibition of nitric oxide synthesis using NOS inhibitors results in increased proliferation of precursors isolated from postnatal mouse SVZ [78].…”
Section: Embryonic Stem Cell Based Therapies For Neurodegenerative DImentioning
confidence: 77%
“…In mammalian brain, NO may regulate neural progenitor proliferation and differentiation by acting in a positive feedback loop with BDNF [22]. Most recently, it was reported that BMP4 regulate cell numbers in the developing neural tube in a NO dependent manner [113]. Consistent with this finding, an independent study reported that inhibition of nitric oxide synthesis using NOS inhibitors results in increased proliferation of precursors isolated from postnatal mouse SVZ [78].…”
Section: Embryonic Stem Cell Based Therapies For Neurodegenerative DImentioning
confidence: 77%
“…The role of BMP signaling has been described in the regulation of cell numbers in the case of hematopoietic stem cells, the other subpopulation of stem cells in the bone marrow [20]. The role of BMP pathway as a cell number regulator has been described even in other systems, such as the chick developing neural tube [21]. In addition, a study indicating a relation between both stem cells populations in the bone marrow niche via BMP signaling has been published [22].…”
Section: Discussionmentioning
confidence: 99%
“…A neurogenetic role for NO has been also described in chicken during development of the neural tube, where NO is involved in the regulation of the balance between cell cycle progression and apoptotic elimination which determines the final size of neural population [39]. From these studies, it appears that NO interacts with other factors involved in the regulation of neurogenesis of the neural tube, with an action in line with its anti-proliferative role [40,41].…”
Section: Nitric Oxide and Neuronal Precursor Proli-feration During Dementioning
confidence: 91%